A multinational study of acute and long‐term outcomes of Type 1 galactosemia patients who carry the S135L (c.404C > T) variant of GALT. Issue 6 (26th September 2022) - Katler, Quinton S.; Stepien, Karolina M.; Paull, Nathan; Patel, Sneh; Adams, Michael; Balci, Mehmet Cihan; Berry, Gerard T.; Bosch, Annet M.; DeLaO, Angela; Demirbas, Didem; Edman, Julianna; Ficicioglu, Can; et al.
Abstract: Patients with galactosemia who carry the S135L (c.404C > T) variant of galactose‐1‐P uridylyltransferase ( GALT ), documented to encode low‐level residual GALT activity, have been under‐represented in most prior studies of outcomes in Type 1 galactosemia. What is known about the acute and long‐term outcomes of these patients, therefore, is based on very limited data. Here, we present a study comparing acute and long‐term outcomes of 12 patients homozygous for S135L, 25 patients compound heterozygous for S135L, and 105 patients homozygous for two GALT‐null (G) alleles. This is the largest cohort of S135L patients characterized to date. Acute disease following milk exposure in the newborn period was common among patients in all 3 comparison groups in our study, as were long‐term complications in the domains of speech, cognition, and motor outcomes. In contrast, while at least 80% of both GALT‐null and S135L compound heterozygous girls and women showed evidence of an adverse ovarian outcome, prevalence was only 25% among S135L homozygotes. Further, all young women in this study with even one copy of S135L achieved spontaneous menarche; this is true for only about 33% of women with classic galactosemia. Overall, we observed that while most long‐term outcomes trended milder among groups of patients with even one copy of S135L, many individual patients, either homozygous or compound heterozygous for S135L, nonetheless experienced long‐term outcomes that were not mild. This was true despite detection by newborn screening and both early and life‐long dietary restriction of galactose. This information should empower more evidence‐based counseling for galactosemia patients with S135L.